G169(P) Dilated Cardiomyopathy – If you don't think about it, you can't diagnose it!. (27th April 2016) - Kanagaratnam, M; Ramesh, P
Abstract : Aims: Dilated or congestive cardiomyopathy refers to congestive cardiac failure due to dilation and systolic dysfunction of the ventricles (predominantly the left ventricle). Initial presentation can sometimes be very non specific or present as simple viral illness. Methods: This is a case of a 17 month old boy who presented with cardiac failure secondary to dilated cardiomyopathy; a number of his symptoms and signs were common to more common child hood conditions such as viral illness or nephrotic syndrome resulting in delay in diagnosis and initiation of appropriate anti failure therapy. Results: A 17 month old boy, weighing 13.4kg presented to his local children's assessment unit due to generally being unwell. He had a history of lethargy, decreased appetite and reduced fluid intake over the past 2–3 weeks. Examination showed mild puffiness around eyes and hands, scattered blanching and non-blanching rash over his back, abdomen and face. No lymphadenopathy or signs of meningism. Chest examination was unremarkable including heart and breath sounds. His abdomen showed soft liver edge 3cm below costal margin. Initial tests showed normal FBC, U&E, CRP, Glucose and urine dip assessment. However his ALT and GGT were elevated at 134 u/L and 64 u/L respectively. Blood gas was normal apart from a raised lactate of 4mmol/L. Ultrasound of his abdomen showed congested liver which prompted a chest x-ray (Figure 1 ). Echocardiography showed reduced EF 24% and dilated ventricles. A diagnosis of severe dilated cardiomyopathy was made. He was transferred to the paediatric intensive care for inotropes and diuretics (Furosemide and Amiloride). He was then transferred to the regional tertiary cardiac centre for further management. Conclusion: Cardiomyopathy should be diagnosed promptly as its outcomes that depend on cause and age at presentation, as well as heart failure status. This boy appeared clinically stable and did not show overt signs of cardiac failure and was treated as possible viral illness before a serious diagnosis was made few days after admission. Every child presenting with symptoms of generally unwell should have a through history and examination to rule out an underlying cardiac pathology.